AB 25. Moxifloxacin pharmacokinetics and pleural fluid penetration in patients with pleural effusion - Chatzika, Kalliopi (Pioneer Bioscience Publishing Company, 2012)
BACKGROUND: Moxifloxacin is widely used for the treatment of parapneumonic pleural effusion or empyema. However, data on moxifloxacin penetration and pharmacokinetics in pleural space have been reported are scarce. The aim of this study was to evaluate the kinetics and penetration of moxifloxacin in patients with various types of pleural effusion and degrees of inflammation. PATIENTS AND METHODS: Seven patients with empyema/parapneumonic effusion (age 52.7±22.2 years) and seven patients with malignant pleural effusion (age 74.3±12.5 years) were included in the study. Moxifloxacin (400 mg) was administered iv as first dose of treatment for patients with empyema/parapneumonic effusion and as single dose in those with malignant effusion. Plasma and pleural fluid samples were collected immediately before and 1, 2, 3, 4, 6, 9, 12, and 24 hours after administration. Moxifloxacin concentration in plasma and pleural fluid was determined by high-performance liquid chromatography (HPLC) with fluorescence detection. The maximum concentration (Cmaxplasma, Cmaxfluid) was estimated by direct observation of determined values at each time point and Tmaxplasma/ Tmaxfluid was the time when those concentrations were achieved. The area under concentration-time curve (AUC(24plasma) and AUC(24fluid)) was calculated by the trapezoidal rule. Penetration of moxifloxacin in the pleural fluid was determined by the AUC(24 fluid/plasma) ratio. The remaining pharmacokinetic parameters were calculated with WinNonlin software. RESULTS: No statistically significant differences were observed between two groups in plasma and fluid Cmax and AUC(24) and the degree of moxifloxacin’s penetration in pleural fluid. The time until the achievement of pleural Cmax was statistically significantly longer in patients with empyema/parapneumonic effusion. The minimum moxifloxacin levels in the pleural fluid at 24 h (Ctrough fluid), were higher in patients with empyema/parapneumonic effusion that in those with malignant effusion but the difference was not statistically significant. CONCLUSIONS: The delay in achievement of pleural fluid maximum moxifloxacin levels and the higher minimum levels in patients with empyema/parapneumonic effusion may be attributed to pleura thickening due to inflammation. However, AUC(24fluid) levels did not differ according to the type of pleural effusion.